Preventive Medicine And Surgery: The Importance Of Modern Approaches And Integration - Tuychiev Golibzhon Urmonzhonovich; Mirkomilova Sug`diyona Abdug`ani qizi (Genius Journals, 2025)
The integration of preventive medicine into surgical practices is becoming a cornerstone of modern healthcare, aiming to improve patient outcomes, reduce surgical complications, and optimize postoperative recovery. Preventive strategies, such as preoperative assessments, infection control, and postoperative care, play a pivotal role in minimizing the risks associated with surgery. This paper examines the importance of combining preventive medicine with surgical procedures and highlights the benefits of this integration. By analyzing evidence-based practices and contemporary approaches, the article demonstrates how preventive measures enhance surgical outcomes, promote patient safety, and reduce the overall burden on healthcare systems.
Keywords: Preventive medicine; Surgery integration; Perioperative care